E-STEM project-based learning in teaching science to increase ICT literacy and problem solving - Syarifah Rahmiza Muzana; Jumadi Jumadi; Insih Wilujeng; Bagus Endri Yanto; Abdul Aziz Mustamin (International Journal of Evaluation and Research in Education (IJERE), 2021)
The aim of the research was to determine the effectivity of implementation of e-learning science, technology, engineering, and mathematics (E-STEM) project-based learning model in teaching science to improve information, communication, and technology (ICT) literacy and problem solving. The study adopted quasi-experimental non-equivalent control group design. E-STEM project-based learning model was applied in experimental classroom, while the control classroom applied conventional teaching. The sample was 46 students who was selected using cluster sampling method. They were in grade VIII academic year 2020/2021 which representing the population students of Junior High School 8, in Aceh Besar, Indonesia. The data were collected using test instrument and questionnaires. Validity verification of instrument measured based on Aiken index, while instrument reliability was determined based on Cronbach’s alpha coefficient. The data were analyzed using Manova and descriptive quantitative. The result of the study showed that there is meaningful difference of ICT literacy and problem solving mean score based on the difference of both teaching approach. It is concluded that the implementation of E-STEM project-based learning model and problem solving in teaching science has significant impact in increasing ICT literacy and problem solving.